AN INVENTORY STUDY ON THE CATEGORIZATION AND TYPES OF RECREATIONAL ACTIVITIES - Taki Can Metin (Fırat University, 2019)
There are many different sources of what recreational activities are and how they should be categorized. The study of Leitner and Leitner (2004) is the most comprehensive of these studies. However, many recreational activities known even in the study have not been mentioned. There are also some problems with the categorization of recreational activities in the study of Leitner and Leitner. There are many reasons why there is no comprehensive study of recreational activities. There is no comprehensive recreational activity inventory that could be a source for many studies due to the large number of recreational activities, the different activities according to the regions, the inaudibility of the activities, and the inconsistencies in the categorization of activities by researchers. This study was carried out with a motivation for recreational activity types and the categorization of these activities. The purpose of the study is to create an inventory list that can serve as a base for the work related to the recreation. In this context, recreational activity types have benefited from secondary data. Expert opinion has been applied to the categorization of recreational activities. As a result, different recreational activity categories were created and an inventory of recreational activity types was revealed. It is thought that this inventory will contribute to all the studies related to recreation. In addition, this study will be able to evaluate the activities that are unknown in terms of practitioners and planners as a recreation opportunity and in parallel with this, it will be possible to integrate new recreation opportunities in the existing plans as well as finding space in practice.